Experimental investigation of FSW induced property changes in welded dissimilar Mg–Al–Zn alloys - Singh U.K.; Dubey A.K.; Saini S.K.; Yusufzai M.Z.K. (My University, 2025)
Intense plastic deformation and intermixing during friction stir welding of dissimilar alloys may suppress the properties in welded zone. To suitably control these changes, careful study is required. Present research investigates microstructure, mechanical performance and corrosion behaviour at different rotational speeds in friction stir welded dissimilar AZ31–AZ91 Mg alloys. Very small cracks were present in welded zone due to formation of magnesium oxide (MgO). The EBSD analysis suggest more concentrated fibre texture at 1000 rpm tool rotational speed as compared to 700 rpm tool rotational speed in welded zone and the texture maximum intensity was 39.447 times of random distribution at tool rotational speed of 1000 rpm. The obtained maximum microhardness was 82 Hv at tool rotational speed of 700 rpm. The maximum values of tensile strength (234.86 ± 7.77 MPa) and flexural strength (350.89 ± 17.67 MPa) of welded samples were decreased as compared to base materials. The corrosion rate of welded samples was increased and corroded surface have some pits and corroded rings. The highest corrosion rate (2.1596 (Formula presented.)) was obtained at 700 rpm. This experimental work suggests that in overall, sample welded at 1000 rpm tool rotational speed has better weld property. © 2024 Informa UK Limited, trading as Taylor & Francis Group.